A Socialization of the Benefits of Brotowali for Health at the Bringkan Lestari Nursing Home in Gresik - RATNA SOFARIA MUNIR; Handayani Handayani; Renny Novi Puspitasari; Nihazzatuzai Nihazzatuzai; Amalia Tauziah; Retno Diah Putri Ekayanti (Journal of Health Community Service, 2025)
Lestari Nursing Home is an active nursing home located in Bringkan village, Menganti sub-district, Gresik district. There are 40 elderly people who are permanent residents. Nursing homes often receive assistance in the form of food or basic necessities. Based on survey results, many elderly people do not know the benefits of the brotowali herbal plant. In fact, brotowali infusion and decoction have been used to treat high blood sugar. Due to the lack of knowledge among the elderly about the benefits of the brotowali herbal plant, the drafting team will hold outreach activities at the Lestari Nursing Home. The aim of this community service activity is to increase the knowledge of the elderly about the benefits of brotowali for health, and increase the awareness of the elderly to use brotowali herbal drinks for natural (herbal) health.  The method used is counseling. The topic given was about the benefits of brotowali for health with a target of 20 elderly people. The results of the counseling showed an increase in knowledge of 84%. The elderly seemed enthusiastic in this outreach activity as seen from their activeness when the question and answer discussion session was opened by the resource person.